Incidence of dynamic seroconversion in subjects received the first dose of the SARS-COV-2 vaccine (AstraZeneca, Moderna and Pfizer) in Kinshasa, Democratic Republic of Congo: prospective cohort study - Mukenge, Eric Kasongo; Sumbu, Blaise Matondo-Manzambi; Nkodila, Aliocha Natuhoyila; Muwonga, Jeremie Masidi; Makulo, Jean-Robert Rissassi; Ngole, Mamy Zita; Bepouka, Ben Izizag; Longokolo, Murielle Mashi; Kamwiziku, Guyguy; Situakibanza, Hippolyte Nanituma; Kayembe, Jean-Marie Ntumba; Longo-Mbenza, Benjamin; et al. (BMC infectious diseases, 2025)
Mass vaccination efforts worldwide have reduced the incidence of COVID-19, but despite this reduction, seroconversion studies in sub-Saharan Africa are limited. The aim of this study is to assess the incidence of seroconversion in subjects who received the first dose of SARS-COV-2 vaccine (AstraZeneca, Moderna and Pfizer) in Kinshasa. This was a prospective study recruiting 918 subjects vaccinated at the Cliniques Universitaires de Kinshasa between 19 April and 14 August 2021. Sociodemographic, haematological, biochemical and serological data were collected. Cox proportional hazards were used to identify predictors of seroconversion with a threshold of p < 0.05. Of the 918 vaccinated individuals, 69.3% were men with a mean age of 47.4 ± 16.0 years. The incidence of seroconversion at last follow-up was 3.00 per 100 P-D. Patients receiving Pfizer (aRR: 3.19; 95% CI: 2.62-3.88) and Modern (aRR: 1.91; 95% CI: 1.60-2.29) vaccines, men (aRR: 2.03; 95% CI: 1.89-3.20), those with comorbidities (aRR: 2.38; 95% CI: 1.89-3.21); subjects with normal creatinine (aRR: 2.08; 95% CI: 1.88-3.32) and normal ALT (aRR: 3.04; 95% CI: 1.89-4.22) were the factors independently predicting seroconversion. The vaccines used had conferred significant immunity on subjects upon receipt of the first dose. This immunity appears to be greater when using the mRNA vaccine than when using the inactivated vaccine.